2018
DOI: 10.3389/fcvm.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Hypoxia-Regulated Non-coding RNAs in Human Primary Endothelial Cells

Abstract: Hypoxia occurs in human atherosclerotic lesions and has multiple adverse effects on endothelial cell metabolism. Recently, key roles of long non-coding RNAs (lncRNAs) in the development of atherosclerosis have begun to emerge. In this study, we investigate the lncRNA profiles of human umbilical vein endothelial cells subjected to hypoxia using global run-on sequencing (GRO-Seq). We demonstrate that hypoxia regulates the nascent transcription of ~1800 lncRNAs. Interestingly, we uncover evidence that promoter-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 82 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…Among the differentially expressed genes and lncRNAs in CAD tissues which from microarray analysis, MAPK1 and MALAT1 were chosen for our research because they were found to be related to CAD in previous studies [4547]. Furthermore, MALAT1 may serve as potential biomarkers of atherosclerosis [48, 49]. MAPK pathways were found playing roles in stroke progression [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Among the differentially expressed genes and lncRNAs in CAD tissues which from microarray analysis, MAPK1 and MALAT1 were chosen for our research because they were found to be related to CAD in previous studies [4547]. Furthermore, MALAT1 may serve as potential biomarkers of atherosclerosis [48, 49]. MAPK pathways were found playing roles in stroke progression [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…This forces the tumor cell to produce ATP through glycolysis and create a lower pH to prevent drug entry 82 . Moreau et al 83 reported that hypoxia can induce the activation of 358 SE regions in tumor cells, and database analysis showed that for 20% of SEs, the closest RefSeq gene was a lncRNA, as exemplified by MALAT1 and LUCAT1. MALAT1 can not only achieve chemoresistance by competitively inhibiting miR-23b-3p or miR-203, but can also bind with EZH2 to regulate CDH1 transcription expression and promote E-cadherin expression and oxaliplatin-induced EMT 84 - 86 .…”
Section: Role Of Se-derived Ncrnas In Cancermentioning
confidence: 99%
“…Lin et al 70 found that after SE-UCA1 activates the Hippo/YAP1 pathway, proliferation and cell survival are simultaneously promoted in ovarian cancer cells, showing some anti-apoptosis characteristics. In addition, Moreau et al 83 found that hypoxia can regulate SE activity, which in turn, mediates tumor apoptosis, and can also activate the expression of some lncRNAs. However, whether SE regulates apoptosis by regulating the expression of lncRNAs has not been further analyzed.…”
Section: Role Of Se-derived Ncrnas In Cancermentioning
confidence: 99%
“…This group aimed to discover changes in the expression patterns of lncRNAs in HUVEC cells exposed to hypoxia and demonstrated that hypoxia affects the transcription of ~1,800 lncRNAs. Among the most relevant lncRNAs identified were MALAT1, HYMAI, LOC730101, KIAA1656, and LOC339803, which were differentially expressed in human atherosclerotic lesions compared to normal vascular tissue (116).…”
Section: Contribution Of Ngs Technologies To the Discovery Of New Ncrnasmentioning
confidence: 99%